The Role of the Hospital Environment in Preventing Healthcare-Associated Infections Caused by Pathogens Transmitted through the Air. (October 2013) - Jacob, Jesse T.; Kasali, Altug; Steinberg, James P.; Zimring, Craig; Denham, Megan E.
OBJECTIVE: To assess and synthesize available evidence in the infection control and healthcare design literature on strategies using the built environment to reduce the transmission of pathogens in the air that cause healthcare-associated infections (HAIs). BACKGROUND: Air can serve as a route for transmission of important HAI pathogens, including Mycobacterium tuberculosis and influenza, and may play a role for others typically transmitted by contact, including Staphylococcus aureus and Clostridium difficile. TOPICAL HEADINGS: Four primary interventions can be used interrupt the transmission of pathogens in air: ventilation, filtration, decontamination, and isolation. Many studies demonstrate that unidirectional airflows, when combined with very clean air and frequent air changes, reduce bacterial counts in the air, though mostly focused on the operating room. A high-efficiency particulate air filter removes almost all particles from the air and is used in protective environments such as the operating room, but little evidence supports its broader application. Ultraviolet germicidal radiation can augment the performance of heating, ventilation, and air conditioning systems. Isolation with negative pressure ventilation prevents spread of airborne pathogens such as tuberculosis. CONCLUSIONS: Current evidence is limited by the complexity of the interactions between pathogens and potential hosts, and in the methods used to assess impact of these strategies. Because the factors that affect transmission of the pathogens are complex and transcend disciplines, a collaborative approach among the key stakeholders in healthcare facility design should be actively pursued from planning to completion of construction and in rigorous research to best determine how design can reduce HAIs.